Teologi Salib Dan Makna Pengorbanan Yesus Bagi Guru Pendidikan Agama Kristen Masa Kini - Br Sinaga, Rut Yesika; Sihombing, Warseto Freddy (Institut Agama Kristen Negeri Tarutung, 2024)
This research focuses on the Theology of the Cross and its relevance for Christian Religious Education teachers, because it is found that currently, there are still very many teachers, especially Christian Religious Education teachers who do not imitate Jesus' sacrifice on the cross. The relationship between Jesus' suffering and Christian teachings becomes the moral foundation and value of love in Christian Religious Education. This study highlights the gap between the meaning of Jesus' sacrifice and current teaching practices in Christian Religious Education, emphasizing the need for further exemplification for teachers. The aim is to describe the Theology of the Cross and how Jesus' sacrifice can be an example for Christian Religious Education teachers in carrying out their duties. This research uses a qualitative method with a desk study approach, collecting information from various sources relevant to the topic. The meaning of Jesus' suffering for Christian Religious Education teachers is an example of unconditional love, sacrifice, and service that needs to be followed in their profession.